Reporting of Concussion Symptoms by a Nationwide Survey of United States Parents of Middle School Children - Zachary Y. Kerr (MDPI AG, 2021)
This cross-sectional study assessed concussion symptom knowledge of parents of middle school (MS) children (aged 10–15 years) through a free-response item that solicited concussion symptoms and compared findings to a pre-validated scale-based measure. A self-administered online questionnaire was sent to a panel of randomly selected United States residents who were recruited by a third-party company, aged ≥ 18 years, and identified as parents of MS children. Via a free-response item, parents listed what they believed were concussion symptoms. Multiple sections later, parents identified potential concussion symptoms via a scale measure, which featured 25 items (22 actual symptoms, three distractor symptoms) with three response options: yes, no, maybe. Free-response item responses were coded into specific symptoms. The 1062 eligible parents that provided complete data commonly identified the symptoms of dizziness (90.2%), blurred vision (87.4%), and balance problems (86.4%) on the scale-based measure. However, these and other symptoms were less commonly identified via the free-response item (dizziness: 44.4%; blurred vision: 16.5%; balance problems: 3.5%). Concussion symptoms commonly reported via the scale-based measure were reported less frequently within the free-response item. Future research must explore strategies to help clinicians working with parents and their children to measure and assess concussion symptom reporting and knowledge.